2011
DOI: 10.1111/j.1442-200x.2010.03296.x
|View full text |Cite
|
Sign up to set email alerts
|

National survey of childhood febrile illness cases with fever of unknown origin in Japan

Abstract: Clarification of illnesses that ought to be differentiated in the diagnostic approach to an FUO case is essential for arriving at its definitive diagnosis by exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In patients with enlarged lymph nodes accompanied with fever, the possibility of necrotizing lymphadenitis should be considered. In a Japanese study13), 14 patients with FUO had necrotizing lymphadenitis, which was the most common diagnosis in 34 patients in the miscellaneous group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients with enlarged lymph nodes accompanied with fever, the possibility of necrotizing lymphadenitis should be considered. In a Japanese study13), 14 patients with FUO had necrotizing lymphadenitis, which was the most common diagnosis in 34 patients in the miscellaneous group.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, in Table 6, we only reviewed the data between 2000 and 2014 from various countries113141516171819202122). Although infectious disease still appears to be the most common cause of FUO in children, it would be interesting to assess for changes in the etiologies of FUO in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although Zhu Futang’s guidelines for FUO suggest to consider temperature, even varying, but maintaining at >37.5°C for more than 2 weeks, in order to avoid missing out those patients who might not show as high as 38.3°C body temperature all the time, but might have other diagnostic indications with body temperature >37.5°C for FUO. We followed the criteria for febrile body temperature of ≥38.3°C either occasionally or persistently for more than 2 weeks to maintain the study in agreement with the previous reports 12. The aetiology of FUO in children mainly includes infectious diseases, non-infectious inflammatory diseases (NIIDs), neoplastic diseases, miscellaneous diseases and undiagnosed diseases 13 14.…”
Section: Introductionmentioning
confidence: 85%
“…The first nationwide retrospective study of FUO in Japan has recently been reported (18). Pediatric case studies of FUO in Japan have also been collectively reported (19). However, accumulating cases of hospi- talized patients meeting the criteria for classic FUO is not easy.…”
Section: Introductionmentioning
confidence: 99%